Global study of football expatriates (2017-2023) - Poli, Raffaele; Besson, Roger; Ravenel, Loïc (Neuchâtel: CIES, 2023)
This report studies the presence of expatriate footballers in 2,200 clubs participating in 135 leagues around the world: 83 from UEFA member associations and 52 from associations belonging to other confederations. In total, we analysed the origin of 62,610 players who were in the first team squad of their employer club on May 1st, including 14,405 expatriates.
Keywords: football; player; migration; geography; spatial anaylsis